2017
DOI: 10.1186/s13018-017-0616-x
|View full text |Cite
|
Sign up to set email alerts
|

Local infiltration of analgesia and sciatic nerve block provide similar pain relief after total knee arthroplasty

Abstract: BackgroundAlthough femoral nerve block provides satisfactory analgesia after total knee arthroplasty (TKA), residual posterior knee pain may decrease patient satisfaction. We conducted a randomized controlled trial to clarify the efficacy of the sciatic nerve block (SNB) and local infiltration of analgesia with steroid (LIA) regarding postoperative analgesia after TKA, when administrated in addition to femoral nerve block (FNB).MethodsSeventy-eight patients were randomly allocated to the two groups: concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
(30 reference statements)
3
14
0
Order By: Relevance
“…The reason for this is due to the multimodal analgesia including PCA pump and LIA which make patients in an acceptable range of pain, thus resulting in a similar degree of pain relief. As for all kinds of peripheral nerve block, LIA has similar pain relief compared with single femoral nerve block [26,27], continuous femoral nerve block [27,28], and single sciatic nerve block [18,20]. However, currently, few studies focus on the comparison between local infiltration analgesia with combined femoral and sciatic nerve block and do not reach a consensus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is due to the multimodal analgesia including PCA pump and LIA which make patients in an acceptable range of pain, thus resulting in a similar degree of pain relief. As for all kinds of peripheral nerve block, LIA has similar pain relief compared with single femoral nerve block [26,27], continuous femoral nerve block [27,28], and single sciatic nerve block [18,20]. However, currently, few studies focus on the comparison between local infiltration analgesia with combined femoral and sciatic nerve block and do not reach a consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that some patients experience significant postoperative pain despite the use of FNB [15,16], due to the fact that the posterior part of the knee is innervated by the sciatic nerve. Since LIA is an alternative, convenient anesthetic technique that is usually performed by orthopedic surgeons [10,17], anesthesia via FNB combined with sciatic nerve block (SNB) and LIA are two major options for supplementing FNB to relieve pain after TKA [18,19]. Recent studies have shown that SNB has similar anesthesia effects and opioid consumption than LIA when combined with FNB [20,21]..…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are some studies that did not report any advantage of LIA with respect to pain reduction and/or morphine consumption in TKA. 8,10,12 Mulford et al presented a double-blinded study comparing LIA and application of a placebo in 2015 investigating postoperative pain scores, 9 no significant difference in postoperative pain scores was found. Nonetheless, LIA might result in a significant reduction in especially high-intensity pain levels postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Because of that, many recent studies evaluated local infiltration analgesia (LIA), with varying results. 1,[5][6][7][8][9][10][11][12][13][14] Continuous quality improvement strategies can reveal insufficient pain management. To compare and then improve pain management, the "Quality Improvement in Postoperative Pain Management" (QUIPS) project is an outstanding tool.…”
mentioning
confidence: 99%
“…Some studies reported that LI analgesia is a safe and effective treatment option for early functional recovery and pain control in TKA. [3][4][5] However, the safety and effectiveness of PNBs have also improved with the spread of ultrasound-guided techniques in combination with nerve stimulus techniques. In recent studies, it has remained controversial which analgesic technique is appropriate for TKA.…”
Section: Introductionmentioning
confidence: 99%